站稳文学的立场: 读林春美《蕉风与非左翼的马华文学》: Stick to The Point of View of Literature: A Critical Review on Chao Foon and the non-leftist Mahua literature - Chin, Ying Xuan (ERUDITE: Journal of Chinese Studies and Education, 2021)
《蕉风与非左翼的马华文学》是林春美今年出版的学术著作，也是目前仅见的《蕉风》专论。从“历史的后见之明的角度回顾”并研究《蕉风》，林春美从三个视角展开她对《蕉风》的探索。另外，她也提出了“非左翼的马华文学”概念。这个概念以及本书的研究视角恰恰让本书站稳了文学的立场。Chao Foonand the non-leftist Mahua literature was the academic work published by Lim Choon Bee this year. It was an academic review about Chao Foon magazines. This book come out with “the non-leftist Mahua literature” concept, and this concept bring the critical work of this book stick to the point of view of literature.Keywords: Chao Foon, Non-leftist, Malayanised, MahuaModernism Literature